(Cy2NH2)2SO4.2SnMe3SO4Cy2NH2; 2(Cy2NH2)2SO4.5SnMe3SO4Cy2NH2: SYNTHESIS AND INFRARED STUDY - DAOUDA NDOYE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Allowing (Cy2NH2)2.SO4.2H2O or Cy2NH2.HSO4 to react with SnMe3Cl in ethanolic media in two specific ratios the sulphato complexes (mentioned in this paper title) were obtained and their infrared study was carried out. Discrete structures containing the complex-anion [SO4(SO4SnMe3)2]4- consisting of a central bidentate sulphate linked to SnMe3 groups which are then coordinated to monodentate sulphate anions or the complex-anion [(SO4)6(SnMe3)5]7- consisting of planar SnMe3 groups, monodentate or bidentate sulphate anions, these complex-anions dimerizing through cations via hydrogen bonds, are suggested.